Comparative Study on The Structure, Physical Properties and Hardness Indentation of a Bulk Fill & An Incremental Composite Resin Restorative Materials (JOURNAL OF ADVANCES IN PHYSICS, 2020)
Totally 80 disk-shaped specimens of Filtek™ Bulk-Fill, 3M ESPE, and Filtek™ Z250 XT, 3M ESPE, were prepared by using split-Teflon mold (4mm×10mm). Specimen characterization XRD, Surface roughness, degree of conversion, Surface microhardness, and depth of cure of the specimens were evaluated after the specimens were stored in distilled water in darkness at 37°C for 24 h. Statistical analysis was done using t-test with a significance level at p